Géographicité et immersion : La réalité virtuelle pour voyager dans le passé - Nicolas Leresche (Cybergeo)
The principle of immersion has been a key factor in the success of many visual attractions since the 19th century, such as the cinema, reaching a new dimension with virtual reality devices for the general public. It is especially because it allows for interaction with the simulated environment, and the powerful sense of reality created by its device, that this technology is used in museum contexts. In addition to the perspectives that its use opens in terms of conservation, its ability to transport the visitor elsewhere and into another time invites us to question its geographicity: does its immersive effect come from an "organizing valence of the space"? Or is it only a simple special effect, as spectacular as it may be? This article aims to identify the modalities of "spectatorial" appropriation of this technology in a heritage context, based on an ethnographic study conducted at a virtual reality installation presented at the Museum of Art and History in Geneva (MAH). It proposes a theoretical framework for the hypothesis of an immersive and instrumented geographicity regime.